PENGARUH STRATEGI PENGORGANISASIAN ISI MATA KULIAH DAN GAYA KOGNITIF TERHADAP HASIL BELAJAR MENGGAMBAR TEKNIK - Selamat Triono (Jurnal Kependidikan, 2005)
Abstract The purpose of this study was to reveal the effect of teaching strategy (organized content: using review and epitome versus conventional text book) toward student’s achievement in reading mechanical engineering drawing subject, and to determine whether students’ cognitive styles affected instruction outcomes. The factorial 2 x 2 research design was used in this study.  The subjects were all students who registered in the first semester of 2004/ 2005 for Mechanical Drawing Class (Menggambar Teknik 1) consisting of 57 students, and randomly divided into two classes. The subjects were tested using Group Embedded Figures Test to reveal their ”field dependent or field independent” cognitive styles. The achievement test in drawing reading was used to determine the effectiveness of teaching strategy. The result of this study indicated that organized content using epitome and review offered viable teaching strategy for teaching drawing reading in mechanical drawing subject. Student cognitive style (field independent or field independent) has significant effect on their learning achievement; however, there was no interaction between the teaching strategy and students’ cognitive styles on the instruction outcome. Keywords: cognitive style and drawing technique